Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Prerequisites - p.4 - Factoring Polynomials - Exercises - Page 39: 42



Work Step by Step

Use: $17z=18z-z$ $-6z^2+17z+3=-6z^2+18z-z+3=6z(-z+3)+1(-z+3)=(6z+1)(-z+3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.